Penyuluhan Penggunaan Spill Kit Sebagai Upaya Pencegahan Healthcare-Associated Infections (HAIS) Pada Cleaning Service di Puskesmas X di Kota Malang - Ani Asriani Basri; Bayyinatun Najjah; Sulafatul Aufa Rosyidah; Ji hasta pronasi (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2026)
Healthcare-Associated Infections (HAIs) are one of the important problems in hospitals that can increase the number of illnesses, length of hospitalization, and health service costs. One of the groups that has the risk of being exposed to the source of infection in the hospital is cleaning service (CS) officers, especially when handling infectious liquid spills. The use of spill kits is one of the infection prevention and control efforts that is important for CS officers to understand. This community service activity aims to increase CS officers' knowledge of the use of spill kits through counseling methods. The activity was carried out at Puskesmas X with pre-test, counseling, demonstration of the use of spill kits, and post-tests. The participants of the activity amounted to 4 CS officers. The results of the activity showed an increase in participants' knowledge after being given counseling. The average pre-test score of 53 increased to 91 in the post-test. This activity shows that counseling is effective in increasing the knowledge of CS officers on the use of spill kits in Puskesmas.